Pemanfaatan Teknologi Informasi dan Komunikasi dalam Mendukung Proses Pembelajaran - Indra Wilian; Nurfuadi (Indonesian Journal of Social Sciences and Humanities, 2025)
The utilization of Information and Communication Technology (ICT) in education has become a crucial componentin enhancing the quality of the learning process. This study aims to explore various ICT implementations inteaching and learning activities based on a literature review. The findings indicate that ICT provides flexibilityin time and space for learners, enriches learning materials, and improves interaction between teachers andstudents. It supports student-centered learning approaches, enables personalized instruction, and accelerates theassessment process. Various digital platforms such as Learning Management Systems (LMS), educational videos,online quiz applications, and virtual discussion forums are widely used to support learning activities. Challenges inimplementing ICT include limited access, digital literacy gaps, and educators' readiness to adopt new technologies.Nevertheless, ICT remains a strategic element in addressing the demands of modern education. With adequatepolicy support, training, and infrastructure, ICT utilization has the potential to enhance the effectiveness andefficiency of learning processes across educational levels. This study emphasizes the importance of synergybetween technology, educators, and educational policies to create an adaptive and innovative learning ecosystem